Diagnóstico de la superación profesional técnica de los profesores de la rama eléctrica - López Collazo, Zeidy Sandra (2018)
The work presents the diagnosis of the initial state of the technical professional improvement of the teachers of the electrical branch of the polytechnic institutes in the province of Artemisa, Cuba. The objective was to characterize the technical professional improvement of the professors of the electrical branch of the polytechnic institutes in the province of Artemisa based on their definition and the determination of dimensions and indicators. To do this, we proceeded to the bibliographic search that made possible the elaboration of the definition of the technical professional improvement of the professors of the electric branch and its operationalization in dimensions and indicators, which were presented in different scenarios, all of which contributed to its redesign and improvement. Different methods were used at the theoretical, empirical and statistical methods that allowed to diagnose this process and to specify the main strengths and limitations. The central tendencies of the state of the dimensions are located in the low evaluative range, far from the central tendency: the cognitive dimension (1,9); the processual dimension (1.99) and the attitudinal dimension (2.75). Weaknesses are recognized in the interinstitutional articulation for the updating, complementation and reorientation of the professional technical content of the professors of the electrical branch, because the potentialities of training as a form of organization are not taken advantage of. The multidimensional correlation coefficient rpj behaved for the dimensions in the (highly coherent) criteria, which allow us to infer with a high degree of probability, that objective and, therefore, reliable analyzes were